Optimization of and experimentation with a bifurcated swing tube strip fertilizer spreading device based on MBD-DEM coupling - Dun, Guoqiang; Sheng, Quanbao; Ji, Xinxin; Li, Xin; Wei, Yuhan; Gao, Shang; Zhang, Chaoxia (Frontiers in Plant Science, 2024)
In order to improve the utilization rate of fertilizers, realize the precise spreading of fertilizers in controllable strips, and ensure the uniformity of fertilizers spreading in both longitudinal and transversal directions, a bifurcated swing tube fertilizer spreading device driven by a spatial hammer pendulum crank mechanism is designed. First, the drive mechanism was designed based on the cylindrical pair of the mechanism. A mathematical model pendulum equation was used to design the swing tube, and the equation of motion of fertilizer particles was established by analyzing the motion and force of fertilizer particles in fertilizer spreading. Secondly, the coupling model based on MBD-DEM was established, and the coupling simulation analysis of the fertilizer spreading process was carried out by using EDEM-RecurDyn software. And the regression equations of three factors and two evaluation indexes were established by the ternary quadratic generalized rotating combination response surface simulation test. The optimization concluded that when the nozzle height is 450.0 mm, the forward is 0.5~0.8 m/s, and the swing frequency is within the range of 1.40~2.00 Hz, the uniformity coefficient of longitudinal fertilizer spreading is ≤25% and the uniformity coefficient of transversal fertilizer spreading is ≤45%. The results of bench validation showed that the errors of longitudinal and transversal fertilizer spreading uniformity coefficients in the bench test were 3.46% and 1.44%, respectively, and the simulation was in good agreement with the bench test. The results of comparative tests show that the uniformity coefficient of longitudinal and transversal of the fertilizer spreading device is reduced by 50.33 percentage points and 14.95 percentage points, respectively, for the bifurcated swing tube compared with that of the single swing tube. It is proved that the bifurcated swing tube strip fertilizer spreading device can achieve the purpose of uniform fertilizer spreading and has better performance than the single swing tube fertilizer spreading. The results and methods of this study can provide a reference for the design of swing tube strip fertilizer spreading device and related fertilizer spreading performance tests.